Enhanced resistive switching performance in yttrium-doped CH3NH3PbI3 perovskite devices. Issue 38 (22nd September 2021) - Luo, Feifei; Ruan, Liuxia; Tong, Junwei; Wu, Yanzhao; Sun, Caixiang; Qin, Gaowu; Tian, Fubo; Zhang, Xianmin
Abstract : In this study, yttrium-doped CH3 NH3 PbI3 and pure CH3 NH3 PbI3 perovskite films have been fabricated using a one-step solution spin coating method in a glove box to construct memristors. Abstract : In this study, yttrium-doped CH3 NH3 PbI3 (Y-MAPbI3 ) and pure CH3 NH3 PbI3 (MAPbI3 ) perovskite films have been fabricated using a one-step solution spin coating method in a glove box. X-ray diffractometry and field-emission scanning electron microscopy were used to characterize the crystal structures and morphologies of perovskite films, respectively. It was found that the orientation of the crystal changed and the grains became more uniform in Y-MAPbI3 film, compared with the pure MAPbI3 perovskite film. The films were used to prepare the resistive switching memory devices with the device structure of Al/Y-MAPbI3 (MAPbI3 )/ITO-glass. The memory performance of both devices was studied and showed a bipolar resistive switching behavior. The Al/MAPbI3 /ITO device had an endurance of about 328 cycles. In contrast, the Al/Y-MAPbI3 /ITO device exhibited an enhanced performance with a long endurance up to 3000 cycles. Moreover, the Al/Y-MAPbI3 /ITO device also showed a higher ON/OFF ratio of over 10 3, long retention time (≥10 4 s), lower operation voltage (±0.5 V) and outstanding reproducibility. Additionally, the conduction mechanism of the high resistance state transformed from space-charge limited current for a Y free device to the Schottky emission after Y doping. The present results indicate that the Al/Y-MAPbI3 /ITO device has a great potential to be used in high-performance memory devices.